Design, development, and implementation of IsoBank : A centralized repository for isotopic data - Shipley, Oliver N.; Dabrowski, Anna J.; Bowen, Gabriel J.; Hayden, Brian; Pauli, Jonathan N.; Jordan, Christopher; Anderson, Lesleigh; Bailey, Adriana; Bataille, Clement P.; Cicero, Carla; Close, Hilary G.; Cook, Craig; et al. (Public Library of Science (PLoS), 2024)
Stable isotope data have made pivotal contributions to nearly every discipline of the physical and natural sciences. As the generation and application of stable isotope data continues to grow exponentially, so does the need for a unifying data repository to improve accessibility and promote collaborative engagement. This paper provides an overview of the design, development, and implementation of IsoBank (www.isobank.org), a community-driven initiative to create an open-access repository for stable isotope data implemented online in 2021. A central goal of IsoBank is to provide a web-accessible database supporting interdisciplinary stable isotope research and educational opportunities. To achieve this goal, we convened a multi-disciplinary group of over 40 analytical experts, stable isotope researchers, database managers, and web developers to collaboratively design the database. This paper outlines the main features of IsoBank and provides a focused description of the core metadata structure. We present plans for future database and tool development and engagement across the scientific community. These efforts will help facilitate interdisciplinary collaboration among the many users of stable isotopic data while also offering useful data resources and standardization of metadata reporting across eco-geoinformatics landscapes.
Keywords: isotopic data; repository